Embryo sac haustorium in Dryas octopetala L. (Rosaceae) - Romana Czapik (Acta Societatis Botanicorum Poloniae, 2014)
The embryo sac haustorium found in Dryas octopetala L. from the Tatra Mts is the first record of its occurrence in Rosaceae. At the eight-nucleate stage of the embryo sac, the antipodal end of the central cell began to grow into a narrow caecum filled with dense cytoplasm and elongated in the chalazal direction leaving the three antipodals in situ. The haustorium enlarged and lost its characteristic shape after the period of fertilization. Finally, the embryo sac occupied almost the whole length of the ovule. Situated at its chalazal end there was either dense cytoplasm with a group of endosperm nuclei or dense, grainy cytoplasm only, if fertilization had not taken place.